2018
DOI: 10.1111/jfpe.12882
|View full text |Cite
|
Sign up to set email alerts
|

Application of high‐pressure argon for improving postharvest quality of cherry tomato

Abstract: The purpose of this study was to investigate the effect of high‐pressure argon on postharvest quality of cherry tomatoes. Physicochemical attributes including weight loss, decay incidence, color changes, firmness, respiratory intensity, titratable acidity (TA), malondialdehyde content (MDA), water status, and antioxidant enzyme activities were analyzed. Flavor characteristics of cherry tomatoes were determined by GC–MS. The results showed that decay incidences of cherry tomatoes subjected to high‐pressure argo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, the L* value of the 80 kV group was significantly lower than that of the control group in the early stage of storage ( p < 0.05), which might be because higher levels of ACP can damage the tomato epidermis [ 33 ]. Feng et al [ 34 ] also found that the L* value of cherry tomatoes treated with high-pressure argon was higher compared with the control group. The a* value of the tomatoes increased in both the control and treatment groups during storage, which suggested that the tomatoes gradually turn red as the storage period extends.…”
Section: Resultsmentioning
confidence: 99%
“…However, the L* value of the 80 kV group was significantly lower than that of the control group in the early stage of storage ( p < 0.05), which might be because higher levels of ACP can damage the tomato epidermis [ 33 ]. Feng et al [ 34 ] also found that the L* value of cherry tomatoes treated with high-pressure argon was higher compared with the control group. The a* value of the tomatoes increased in both the control and treatment groups during storage, which suggested that the tomatoes gradually turn red as the storage period extends.…”
Section: Resultsmentioning
confidence: 99%
“…cerasiforme cv. ) consist of beneficial nutrients, such as minerals, vitamins, phenolic compounds, and lycopene [ 1 ]. However, cherry tomatoes deteriorate rapidly without proper preservation, and thus their shelf life ranges from only 5 to 7 days after harvest [ 2 ].…”
Section: Introductionmentioning
confidence: 99%